2006
DOI: 10.1182/blood-2006-04-017046
|View full text |Cite
|
Sign up to set email alerts
|

Selective leukemic-cell killing by a novel functional class of thalidomide analogs

Abstract: Using a novel cell-based assay to profile transcriptional pathway targeting, we have identified a new functional class of thalidomide analogs with distinct and selective antileukemic activity. These agents activate nuclear factor of activated T cells (NFAT) transcriptional pathways while simultaneously repressing nuclear factor-B (NF-B) via a rapid intracellular amplification of reactive oxygen species (ROS). The elevated ROS is associated with increased intracellular free calcium, rapid dissipation of the mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 52 publications
1
33
0
2
Order By: Relevance
“…Both CPS49 and flavopiridol have been shown to alter the redox status of leukemic cells (Decker et al, 2001;Ge et al, 2006). To assess the selective combined influence of CPS49 and flavopiridol on the redox properties of primary and transformed cells the intracellular levels of ROS and GSH were assessed in cells treated with different combinations of flavopiridol and CPS49 after 1-and 16-h incubations, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both CPS49 and flavopiridol have been shown to alter the redox status of leukemic cells (Decker et al, 2001;Ge et al, 2006). To assess the selective combined influence of CPS49 and flavopiridol on the redox properties of primary and transformed cells the intracellular levels of ROS and GSH were assessed in cells treated with different combinations of flavopiridol and CPS49 after 1-and 16-h incubations, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds inhibit NF-B activity, increase intracellular calcium, and produce a rapid elevation of intracellular ROS that results in dissipation of the mitochondrial membrane potential and subsequent caspase-independent necrotic cell death (Ge et al, 2006). The shared targeting of both NF-B activity and mitochondrial function by flavopiridol and the redoxreactive thalidomides suggested that the combinatorial use of these agents may produce more effective tumor cell killing.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Előzetesen megállapítottuk, hogy a talidomid analógjaink bejutva a sejtbe kölcsönhatásba lépnek a lipid cseppecskékkel és az endoplazmatikus retikulummal, ezért megvizsgáltuk, hogy az Ac-915 és az Ac-2010 anyagoknak van-e oxidatív stresszt kiváltó hatása, ahogy azt Ge és mtsai munkájuk során találták az ún. "redox-reaktív" talidomid analógokról [85]. Megmértük a két talidomid analógunkkal való kezelést követően a ROS szintet Hep3B sejtekben (9.a ábra).…”
Section: Az Ac-915 éS Ac-2010 Hatása Az Intracelluláris Antioxidáns Runclassified